Application of enzymes in compound feeds - Spring W.G.; Gadient M. (Feed manufacturing in Southern Europe: New challenges, 1997)
Several aspects of enzyme applications are presented. Most enzyme products are available in two physical forms, dry powders and water soluble liquids. Powders are expected to be free-flowing, easy to mix and stable, whereas liquids should be non-viscous and stabilised. Also, handling of enzymes in feedmill and aspects related to quality controls are presented and discussed. Finally, the author mentions that two characteristics, common to many enzymes, allergic potential and susceptibility to hydrothermal processes, require attention when handling products in feedmill. In consequence, firstly, protective measures should be used when handling enzymes and dust formation avoid. Secondly, where significant losses occur during pelleting and expansion, enzymes may be applied in liquid forma post-pelleting.
South European Feed Manufacturers Conference, 1996/05/09-11, Reus (Spain)